1995
DOI: 10.1073/pnas.92.16.7430
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acids exhibit anthozoan "host factor" activity: they induce the release of photosynthate from symbiotic dinoflagellates in vitro.

Abstract: Reef-building corals and other tropical anthozoans harbor endosymbiotic dinoflagellates. It is now recognized that the dinoflagellates are fundamental to the biology of their hosts, and their carbon and nitrogen metabolisms are linked in important ways. Unlike free living species, growth of symbiotic dinoflagellates is unbalanced and a substantial fraction of the carbon fixed daily by symbiont photosynthesis is released and used by the host for respiration and growth. Release of frxed carbon as low molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 18 publications
(21 reference statements)
3
74
0
Order By: Relevance
“…The only previous study of NO in clade C Symbiodinium (Hawkins and Davy 2012) reported a temperature-induced downregulation of NO synthesis. This could be due to the use of cultured Symbiodinium cells rather than those sampled in hospite, as their physiology is likely to be different outside the host (Gates et al 1995). The nature of the treatments-rapid heating in the previous study versus a 1°C d -1 rate here-may also have contributed, as could sub-cladal differences in symbiont physiology.…”
Section: Discussionmentioning
confidence: 75%
“…The only previous study of NO in clade C Symbiodinium (Hawkins and Davy 2012) reported a temperature-induced downregulation of NO synthesis. This could be due to the use of cultured Symbiodinium cells rather than those sampled in hospite, as their physiology is likely to be different outside the host (Gates et al 1995). The nature of the treatments-rapid heating in the previous study versus a 1°C d -1 rate here-may also have contributed, as could sub-cladal differences in symbiont physiology.…”
Section: Discussionmentioning
confidence: 75%
“…There is ample evidence that host homogenate can stimulate release of photosynthetic products from symbiotic algae of giant clams, anemones, zoanthids and corals (Cook and Davy, 2001;Gates et al, 1995;Grant et al, 1997;Ishikura et al, 2004;Sutton and Hoegh-Guldberg, 1990;Trench, 1971). While a beneficial effect appears to be only valid for symbiotic and not for aposymbiotic hosts (Trench, 1971), there is also evidence for adverse effects of certain host homogenates (e.g., Sutton and Hoegh-Guldberg, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A synthetic cocktail representing the free amino acid pool measured in the coral P. damicornis (Gates et al, 1995), temporarily stabilized in vitro cultures of P. compressa symbionts. Incubation with host specific free amino acid cocktails (including the sulfonic acid taurine) in micro-to millimolar range can have a stimulating effect on fixation or release of carbon (Biel et al, 2007;Cook and Davy, 2001;Gates et al, 1995;Stat et al, 2008b;Wang and Douglas, 1997). While the general alleviating effect on physiological parameters of freshly isolated symbionts has been clearly demonstrated, its effect size is clade dependent (Gates et al, 1999;Stat et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, studies have investigated the photophysiology of Symbiodinium either alone in culture, in culture with host factor (coral animal amino acids; Gates et al 1995), or in hospite. However, because most corals selectively associate with certain Symbiodinium clades (Goulet 2006), comparative studies of symbiont physiology within or isolated from a single host are less common.…”
Section: Physiological Differences Associated With Different Symbiontmentioning
confidence: 99%